2010
DOI: 10.1049/iet-rpg.2009.0190
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the influence of the distance between two wave energy converters on energy production

Abstract: In this paper, an array of two interacting wave energy converters with hydraulic PTOs is considered. A time domain model is derived by using classical linear potential theory. Numerical simulations and parametric studies are performed in order to determine the influence of the distance on the capture width of each system in the array, both in regular and irregular waves. It is shown that when the systems are close, the front system (which meets the waves first) is more affected by the wave interaction than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…A similar discussion is carried out in [32], where further development accounts for the effects of radiation at closer distances; although the authors provide a model for the approximation of the interaction factor as function of the separating distance, the effect of radiation on the interaction between WECs was not isolated from the effect of diffraction. Separation between the effects of diffraction and radiation on the energy absorption have been considered in Babarit et al [34], where the problem has been studied by considering a two-body array and keeping one device fixed, inhibiting radiation. Consider a two-body array with no incoming waves, with the first device (WEC 1) induced to oscillate by means of a prespecified PTO force , and the second device (WEC 2) to be optimally controlled so as to absorb the maximum amount of energy radiated by the first device.…”
Section: Discussionmentioning
confidence: 99%
“…A similar discussion is carried out in [32], where further development accounts for the effects of radiation at closer distances; although the authors provide a model for the approximation of the interaction factor as function of the separating distance, the effect of radiation on the interaction between WECs was not isolated from the effect of diffraction. Separation between the effects of diffraction and radiation on the energy absorption have been considered in Babarit et al [34], where the problem has been studied by considering a two-body array and keeping one device fixed, inhibiting radiation. Consider a two-body array with no incoming waves, with the first device (WEC 1) induced to oscillate by means of a prespecified PTO force , and the second device (WEC 2) to be optimally controlled so as to absorb the maximum amount of energy radiated by the first device.…”
Section: Discussionmentioning
confidence: 99%
“…Constrained control of an array of 12 closely spaced, heaving-point absorbers is studied in [183] and [184], where the interbody distance is just 1.3 times the diameter of the WEC. An array of two heaving cylinders with a nonlinear PTO is considered in [185], where several values of the hydraulic precharge pressure are compared, to find an optimal relation between PTO precharge pressure and incident wave period.…”
Section: Control Of Wave Farmsmentioning
confidence: 99%
“…Random arrays were formulated and tested, and it was found that using different dimensions of point absorbers within an array can produce more power through the increased power to mass ratio. Babarit, et al [76] studied the effect of the distance between two-point absorbers connected to hydraulic PTOs on their energy production as seen in Figure 7. It was noticed that both radiation and diffraction forces contribute similarly to the interactions between the two buoys.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Figure 7. Schematic of the two-buoys studied by [76] to check the effect of the interactions on the power capture.…”
Section: Theoretical Developmentmentioning
confidence: 99%